The Effect of Candlenut (Aleurites Moluccana I Willd.) Seed Flour in Native Chicken Feeding Toward the Internal Egg Quality and Cholesterol Contens - Jein Rinny Leke; Florencia Sompie; Betty Bagau; Albert Podung; Cherlie Sarajar; Ratna Siahaan; Endang Pudjihastuti; Eko Widodo (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2022)
The research aimed to examine effects of Aleurites moluccana (L.) Willd. (Candlenut) Seed Flour used in feed toward egg quality and cholesterol contents of egg-laying native chicken. The research method used was Completely Randomized Design and was continued with Duncan’s test if significant different present. There were 5 treatments comprising of R0 = 100 % of Basal Diet (BD), R1 = 98.5% of Basal Diet (BD) + 1.5 % of Candlenut Seed Flour (CSF), R2 = 97 % of Basal Diet (BD) + 3% of CSF, R3 = 95.5% of Basal Diet (BD) + 4.5 % of CSF, R4 = 94% of Basal Diet (BD) + 6 % of CSF and replications, of which each replication consisted of 8 egg-laying native chickens. In addition, 50 eggs derived from egg-laying native chickens were taken weekly for quality analysis. Variables of this research were egg weight (g/egg), albumen (g/egg), yolk colour, yolk weight (g/egg), egg yolk cholesterol (mg/100g), blood cholesterol (ml/dl), blood LDL (ml/dl), blood HDL (ml/dl), and blood triglycerides (ml/dl), and egg shell’s weight (g/egg) and thickness (mm). As a result, the effects of CSF up to 6 percent of feeding had significant result (P<0.01) to egg’s weight, albumen, yolk colour, yolk weight, cholesterol, blood cholesterol, blood LDL, blood HDL and blood triglycerides, but not significant (p>0.05) on egg shell’s weight and thickness. Therefore, the use of 6 % of Candlenut) Seed Flour in feed had positive effects to improve egg quality and cholesterol contents of egg-laying native chicken.